PERTANGGUNGJAWABAN NEGARA PENGIRIM ATAS PENYALAHGUNAAN HAK KEKEBALAN DAN KEISTIMEWAAN OLEH PEJABAT DIPLOMATIK (STUDI KASUS PERBUDAKAN MODERN TERHADAP IMIGRAN FILIPINA OLEH PEJABAT DIPLOMATIK ARAB SAUDI DI INGGRIS) - Juanito Stevanus; Maria Maya Lestari; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Immunities and privileges of change offices aim to support performance and to avoidintervention from parties. Being unable to be arrested and immune from the power of law,whether criminal, civil law, or administrative law, is a form of impunity for destruction. Inthis thesis the case of protecting the rights of protection that occurred in England involvedthe replacement of a Saudi Arabian gun named Khalid Basfar. The official who overlaid ithad protected his right of immunity for exploiting his right to licence and traffic in humanbeings to his domestic worker named Josephine Wong. The domestic worker from thePhilippines also did not receive her wages while working at Basfar's residence. Freedom toprotect protections like this makes it necessary for the sending country to take legalresponsibility for the reduction.The research method used in this research is normative legal research. This researchis library law research. The focus of the discussion of this research is related to legalprinciples. The data sources used are primary, secondary and tertiary legal sources. In thislegal research, researchers use a case approach which will examine the 1961 ViennaConvention on Diplomatic Relations, the 1961 Vienna Optional Protocol, to the 2000Palermo Protocol on Trafficking in Persons.The result obtained is that there is an urgency for the responsibility of the sendingcountry in responding to the issue of securing immunity which can create better relationsbetween the receiving country and the sending country and the victim country. The forms thatare expressed in simple terms are the responsibility of the sending country, both in the formof recalling and removing the immunity from restrictions. This research also describes thelegal remedies that can be taken by the receiving country and the victim country.Keywords: Diplomatic Immunity, Slavery, State Accountability